A SIMPLE AND FAST RP-UHPLC-PDA METHOD FOR DETERMINATION OF ISRADIPINE FROM POLYMERIC NANOCAPSULES - Barbosa, Fernanda Malaquias; Camargo, Guilherme dos Anjos; Lyra, Amanda Martinez; Nadal, Jessica Mendes; Farago, Paulo Vitor (Asian Journal of Pharmaceutical and Clinical Research, 2020)
A simple and fast analytical method of ultra-high performance liquid chromatography (UHPLC) was developed and validated in order to assay isradipine in poly(ε-caprolactone) (PCL)/polyethylene glycol (PEG) nanocapsules. Experiments were performed by UHPLC on a C18 chromatographic column at 25°C using a mobile phase composed by methanol and water (85:15 v/v) with a flow rate of 0.5 mL.min−1 and UV detection at 327nm for achieving a total run time of 1.5 min. The UHPLC method was validated according to the guidelines set on The International Conference on Harmonisation. It proved to be selective, linear (r = 0.99962), precise (RSD < 4.1%), and accurate (recovery rates between 95.24 and 96.53%) at the range from 10 to 40 µg.mL−1. The performance was robust when slight changes in the flow rate, wavelength of detection, and mobile phase composition were tested. It was successfully applied to quantify isradipine from nanoparticulate polymeric systems, showing high loading efficiency rates, greater than 98.55%. These results provided an experimental basis to use this method for quantifying isradipine with reliable results, besides being very fast, easy to perform and cheaper.